Nierówność płci w wychowaniu i resocjalizacji młodzieży w perspektywie badań przedstawicieli oświaty, resocjalizacji i pracy socjalnej - Kacała , Karolina (Studia Edukacyjne, 2023)
My interest in issues of social inequality, in particular gender inequality, as well as my desire to understand the gender differences I observed in the causes of girls’ placement in the Youth Education Centre, contributed to my research and this follow-up article. Studies have been carried out as qualitative research. The researcher, applying an instruction manual, interviewed eight representatives of education, resocialization, and social work. The interviews concerned social inequality and the situation of contemporary youth. The main research problem was the question of how representatives of education, resocialization, and social work perceive girls’ and boys’ behaviour and correction applied to them due to gender? Analysis and interpretation of the interviewees’ opinions indicated a meaning of the internalized gender image. Moreover, the research can help realize that the disproportionately high number of women working in education, resocialization, and social issues has an impact on the reproduction of cultural patterns and social standards, which further consolidates gender inequality.